A Case Report of Giant Hepatic Hemangioma in A Patient with Budd-Chiari Syndrome - M Aliakbarian (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: Giant hemangiomas are less likely to be present at birth. This syndrome is caused by obstruction of the portal veins of the liver and requires surgical intervention. Treatment of hepatic hemangiomas varies depending on the symptoms, location and size. In this study, giant hepatic hemangioma in a patient with Budd-Chiari syndrome was reported. CASE REPORT: The patient is a 57-year-old woman with a giant hemangioma in the liver who has referred to Montaserieh Hospital in Mashhad with symptoms of liver failure, anorexia and early satiety and obstruction of hepatic portal veins. She did not mention any specific drug or food allergies. Except for the heartbeat, all other vital signs were in the normal range. Initial examinations diagnosed giant liver hemangiomas and ascites. After performing the required diagnostic tests, the liver weighing about 10 kg was removed and a liver transplant was performed. After 13 days, the patient was discharged in good general condition. CONCLUSION: One of the rare indications for liver transplantation is giant hepatic hemangioma, which causes liver dysfunction and Budd-Chiari syndrome. Liver transplantation in these patients improves their life and shows good results.